Youth leisure-time physical activity from the perspectives of young adults with visual impairments - Haegele, Justin (European Journal of Adapted Physical Activity, 2019)
The purpose of this study was to examine the meaning that young adults with visual impairments ascribe to their youth leisure-time physical activity experiences. This study adopted an interpretative phenomenological analysis (IPA) research approach. Ten participants (aged 21-34 years; eight women, two men) with visual impairments were included in this study. Semi-structured, audio-taped telephone interviews acted as the primary source of data for this study. Data were analyzed thematically using a four-step process informed by IPA and three interrelated themes were constructed: (a) "I just always felt normal when I was doing them": Preferences for unstructured activities, (b) "They didn't baby me": Importance of supportive parents, and (c) ""They didn't know how to deal with my disability": Comparing stakeholders in integrated versus self-contained sport". The participants described a strong preference for unstructured physical activities and reported that support from parents was critical in allowing them to enjoy physical activities during youth.
Keywords: Blindness; Exercise; Phenomenological; Adapted Physical Activity